The Invisible Assistant: How to Know If Your Doctor is Using AI - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI in healthcare represents a quiet, yet profound, revolution in clinical practice. For the average patient, this ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care